2008
DOI: 10.1103/physrevlett.101.266404
|View full text |Cite
|
Sign up to set email alerts
|

Signature of Quantum Criticality in Photoemission Spectroscopy

Abstract: A quantum phase transition in a heavy-fermion compound may destroy the Fermi-liquid ground state. However, the conditions for this breakdown have remained obscure. We report the first direct investigation of heavy quasiparticle formation and breakdown in the canonical system CeCu(6-x)Au(x) by ultraviolet photoemission spectroscopy at elevated temperatures without the complications of lattice coherence. Surprisingly, the single-ion Kondo energy scale T(K) exhibits an abrupt step near the quantum critical Au con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
52
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 28 publications
8
52
0
Order By: Relevance
“…24,25 In many cases, it is observed that the Kondo temperature scale vanishes at the approach to QCP. 23,26 The results in the present study reveal finite Kondo temperature scale at the QCP in the solid solution Ce 2 Rh 1−x Co x Si 3 suggesting that the magnetic Ce 4f electrons near QCP acquire itineracy at lower temperatures -the antiferromagnetism near the QCP occurs among the itinerant electrons and hence indicates the applicability of an SDW picture in these cases. 9,15 Interestingly, the results in Fig.…”
supporting
confidence: 51%
“…24,25 In many cases, it is observed that the Kondo temperature scale vanishes at the approach to QCP. 23,26 The results in the present study reveal finite Kondo temperature scale at the QCP in the solid solution Ce 2 Rh 1−x Co x Si 3 suggesting that the magnetic Ce 4f electrons near QCP acquire itineracy at lower temperatures -the antiferromagnetism near the QCP occurs among the itinerant electrons and hence indicates the applicability of an SDW picture in these cases. 9,15 Interestingly, the results in Fig.…”
supporting
confidence: 51%
“…CEF resonances.-CEF satellite structures in heavyfermion systems have been previously observed by photoemission [19][20][21] and scanning tunneling [22,23] spectroscopy. In order to understand their impact, one must realize that CEF resonances originate from the same strong correlation effect that generates the low-energy Kondo resonance itself [20,24].…”
mentioning
confidence: 90%
“…The sample temperature during the measurements was varied between room temperature (RT) and approximately 20 K (see Ref. 21 for details). Substrate preparation (sputtering and annealing [22]), surface characterization by low-energy electron diffraction (LEED) and x-ray photoemission spectroscopy (XPS), and deposition of the molecules from a Knudsen cell [23] have been done at RT and in situ.…”
mentioning
confidence: 99%
“…2 shows the result of a quantitative line width analysis. The individual values for the full width at half maximum (FWHM) were obtained by a two step analysis: To restore the photoemission signal above E F , the spectra have been normalized to the Fermi-Dirac distribution (FDD) [21,[37][38][39][40] first, and then fitted by a Lorentzian, which describes the line shape of the peak reasonably well (see inset of Fig. 2).…”
mentioning
confidence: 99%